Analysis of geodetic control points density depending on the land cover and relief – the Opoczno district case study - Pokonieczny, Krzysztof; Bielecka, Elzbieta; Kamiński, Paweł (International Conference “Environmental Engineering”, 2017)
The main goal of this study is an analysis of statistical and spatial relationships between land cover, relief and geodetic control points’ location. We aimed at proving the previous results showing that in rural areas the density of horizontal geodetic points depends at least 50% on the land cover. Moreover, two clustering methods, k-means and Kohonen self-organising maps, were used to group surveying districts according to similarity in land use, relief and geodetic control density. The research methods includes statistical methods, ie. Pearson correlation and coefficient of determination computed by Pawlowski method as well as spatial autocorrelation expressed by Moran I global index. The results show that both clustering methods give very similar results, however for the k-means the surveying districts are more spatially clustered, than for Kohonen. The coefficient of determination R2 equals 0.652, what means that geodetic control points density in 65.2% explains by the percentage of built-up areas, forests and the standard deviation of elevation. The analysis was conducted for the 3rd order geodetic control points, for Opoczno district, located in the central part of Poland.
Keywords: cluster analysis; geodetic control; k-means; computational intelligence methods; topography